Application of Multi-agent system in College Searching for Fresher’s Recruitment System (International Journal of Engineering and Computer Science, 2017)
The proficiency of Multi Agent imposes us to use its features to design an approach towards constructing a system for Recruitment of Fresher. Using any single agent we cannot perform complex activities of candidates requirement so we use distributed problem solving approach and utilize it with multi-agent to perform each step towards building FRS. Here we assist our system to get input request by company for the recruitment of candidates then our system provides a list of eligible candidates for the recruitment process of company on the basis of pre-conditions and parameters given by the company. We also use some cognitive parameters (like) which make our agents proactive in selection of zone then state and then colleges.